Pendekatan Kedwibahasaan dalam Pengajaran Bahasa Indonesia pada Siswa Kelas Rendah - Eti Ramaniyar; A A Alimin (JP-BSI (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2020)
The purpose of this study is to describe the application bilingual approach in teaching Indonesian subjects to lower elementary school  of SDN 15 Sempalai Tebas. This research is focus on field research using sociolinguistic studies. The object of this research is teachers and low-grade elementary school students. The data collection techniques used in this study were direct observation techniques, free listening and in-depth interviews. Tools used in data collection are: a. observation guide and field notes, b. Audio visual recording equipment, and c. Interview guide. The data were analyzed by using interactive analysis of the Milles and Huberman model. The results showed that the bilingual approach was used by the teacher in the learning process. The teacher applies a bilingual approach in the learning process by using the Malay Language with Sambas dialect Dialect, alternately with Indonesian Language. In teaching and learning activities when the teacher explains the subject matter to students, Indonesian language uses in speech of simple vocabulary, while the Malay Language with Sambas Dialect is used in the complex vocabulary in the learning process at the classroom.